Synthesis of Silver Nanoparticles Using Lyngbya Majuscula Extract and their Antibacterial Effects - Nallusamy Duraisamy; Sakthivel Muthu; Kathiravan Krishnan (International Journal of Pharma and Bio Sciences, 2020)
Green chemistry approaches to find extensive application in the biosynthesis of metallic nanoparticles, due to its readily abundant nature, Sustainable materials were used as a base material for the synthesis of nanoparticles. Herein, we have established a simple, eco-friendly, low-cost, and photo-light induced biosynthesis (PLNB) of silver particles blue green algae extract from Lyngbya majuscula. The physicochemical characteristic of PLNB-AgNPs was characterized by various spectroscopic and microscopic techniques such as UV-spectroscopy, Fourier transform infrared spectroscopy (FT-IR), Zeta ζ-potential analyzer, High-resolution transmission electron microscopy (HR-TEM), and Atomic force microscopy (AFM). The size of the synthesized AgNPs was found to be 16 nm. The antibacterial efficacy of the AgNPs obtained and biosynthesized from L. majuscula was evaluated and compared with known antibiotics streptomycin and erythromycin which was used as control against gram negative and gram positive bacteria, respectively. The membrane permeability results of AgNPs showed that the antibacterial activity with inhibition of 99% on E. coli (18 μg/mL) and B. cereus (23 μg/mL). The morphological changes and cell membrane damage AgNPs induced by a microbial cell were evaluated by AFM microscopic analysis. The membranes were disrupted in the cells of E. coli and B. cereus treated with biosynthesized AgNPs and showed that shrunken membrane and with oozed out cytoplasmic content were found attached on the cell surface. The results of this study showed that AgNPs could effectively inhibited the bacterial strain E. coli and B. cereus. Hence the AgNPs could be used in food packaging material and bio-sensing microbial presence in food samples.